Word Formation Process on Best Seller Food Brand Name in Grab and Go-Jek Application - Nur Fitria Anggrisia; Ilma Rosyidah; Aning Riza (JETLe (Journal of English Language Teaching and Learning), 2020)
This research aims at describing how bestseller food brand names in Grab and Go-Jek Application are created. To analyze the data found, the researchers applied English word formation in English morphology. The researchers used descriptive research. The data were bestseller food brands which found in Grab and Go-Jek Mobile Application. It is a kind of Application which provides delivery foods. The data were only taken from the 2019 period of those applications. The researcher found that the best seller food brand names in the Grab and Go-Jek application can be created by applying word formation such as compounding, borrowing, reduplication, abbreviation, acronym, and clipping.